Curriculum Innovation in English Language Education: A Comparative Study - Jamiatul Hasanah; Gumarpi Rahis Pasaribu (Yayasan Insan Cipta Medan, 2025)
This study explores the implementation and impact of curriculum innovation in English language education at SMA Negeri 1 Padang Sidimpuan. Against the backdrop of national curriculum reforms and global educational trends, this research investigates how curriculum innovation is interpreted and practiced by English teachers, and how it influences teaching effectiveness and student learning outcomes. Employing a qualitative approach with case study methods, data were gathered through interviews, classroom observations, and document analysis. The findings reveal that innovative practices—such as the integration of technology, contextualized learning materials, and student-centered pedagogy—are being implemented to varying degrees. However, several challenges persist, including limited teacher training, inconsistent access to resources, and misalignment between innovation goals and assessment practices. The study concludes that successful curriculum innovation depends not only on policy directives but also on teacher agency, institutional support, and continuous professional development. This research contributes to the growing discourse on English curriculum transformation and offers recommendations for sustainable, context-sensitive innovation in secondary language education.